(x+2) do kwadratu +2(x-1)do kwadratu - (x-3)(x+3)
3(x+3) do kwadratu -(x+4) do kwadratu +(x-2)(x+2)
2(2a-3)do kwadratu - (2a+3)do kwadratu-5(a+2(a-3)
5(1-y) do kwadratu -(3+y)do kwadratu -3(1+y)(1-y)
(z+y)+2z+(z-3y) do kwadratu
(a-b)do kwadratu +(a+b) do kwadratu
(2a+b ) do kwadratu - (a-2b) do kwadratu
Pomozcie do 16:30

1

Odpowiedzi

2010-01-05T16:52:13+01:00
(x+2)²+2(x-1)² - (x-3)(x+3)=x²+4x+4 +2x²-4x+2-(x²+9)=
x²+4x+4+2x²-4x+2-x²-9= 2x²-3

3(x+3) do kwadratu -(x+4) do kwadratu +(x-2)(x+2)=
3x²+12x+27-x²+16x-16+x²-4=3x²+28x+7

2(2a-3)do kwadratu - (2a+3)do kwadratu-5(a+2(a-3)=
8a²-24a+18-4a²-12a-9-5a²+5a+30=
a²-31a+39

5(1-y) do kwadratu -(3+y)do kwadratu -3(1+y)(1-y)=
5-10y+y²-9-6y-y²-3+3y²=3y²-13-7

(z+y)+2z+(z-3y) do kwadratu=


(a-b)do kwadratu +(a+b) do kwadratu =
a²-2ab+b²+a²+2ab+b²=2a²+2b²

(2a+b ) do kwadratu - (a-2b) do kwadratu=
4a²+4ab+b²-a²-4ab-4b²=3a²-3b²